PENGEMBANGAN BAHAN AJAR DIGITAL BERBASIS KEARIFAN LOKAL MENGGUNAKAN GENIALLY PADA MATA PELAJARAN IPAS KELAS IV SD NEGERI 79 PALEMBANG - Kusuma, Muhammad Ilham; Nur Syafarudin; Sugiarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a local wisdom-based digital teaching material using Genially for IPAS (Natural and Social Sciences) subject in Grade IV of SD Negeri 79 Palembang. The research method used is Research and Development (R&D) with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The validity assessment was carried out by three validators consisting of lecturers and classroom teachers, obtaining an overall validity percentage of 90.6% with the category of